The Rhox genes - MacLean, James A (Reproduction, 2010)
Homeobox genes encode transcription factors that have crucial roles in embryogenesis. A recently discovered set of homeobox genes - the Rhox genes - are expressed during both embryogenesis and in adult reproductive tissues. The 33 known mouse Rhox genes are clustered together in a single region on the X chromosome, while likely descendents of the primodial Rhox cluster, Arx and Esx1, have moved to other positions on the X chromosome. Here, we summarize what is known about the regulation and function of Rhox cluster and Rhox-related genes during embryogenesis and gametogenesis. The founding member of the Rhox gene cluster - Rhox5 (previously known as Pem) - has been studied in the most depth and thus is the focus of this review. We also discuss the unusually rapid evolution of the Rhox gene cluster.